Language learning in virtual worlds - Saba, Riad (2013)
Language Learning has utilized technology for decades, and while world-wide social dynamics place more demands for language learning, there has not been a widespread use of a specific technology as the dominant medium for language learning. In the meanwhile, Virtual Worlds technology emerged during the last two decades as an immersive technology that offers an online representation of reality, allowing user interaction with the surrounding environment including objects and other users through Internet-enabled desktop personal computers. Since their introduction, Virtual Worlds have grown in popularity, and are now utilized by a large online community as social and gaming environments. Over two decades of research have shown the potential of Virtual Worlds for learning in various fields, but very few empirical studies have been dedicated to explore Virtual Worlds for language learning.